Deskripsi Kemampuan Bahasa Reseptif Anak Usia (5-6 Tahun) Di TK Negeri Pembina Kecamatan Kota Tengah Kota Gorontalo - Mifta Huljanah. Lakamaru; Sri Wahyuningsi Laiya; Rapi Us. Djuko (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
The purpose of this study was to determine the receptive language ability of children aged (5-6) years in the Pembina State Kindergarten, Kota Tengah District, Gorontalo City. The researcher conducted a qualitative research method discussing the receptive language ability of children aged (5-6) years. The subjects of this study were three children and one teacher of the Pembina State Kindergarten. Data were collected through interviews and documentation. Data analysis was carried out by data reduction, data presentation and drawing conclusions. The results of the study conducted at the Pembina State Kindergarten, Kota Tengah District, Gorontalo City aimed to see a child's ability to understand and process language received from others. The research activities were carried out for approximately 1 month. In writing this thesis, the author aims to describe the receptive language ability of children aged 5-6 years. The importance of optimizing aspects of child development including aspects of language development from an early age considering that at that time the child's brain is at an unlimited potential to be developed, children must be given the opportunity to develop their abilities with various fun learning activities.